Stretchable array of metal nanodisks on a 3D sinusoidal wavy elastomeric substrate for frequency tunable plasmonics. (14th February 2017) - Feng, Di; Zhang, Hui; Xu, Siyi; Tian, Limei; Song, Ningfang
Abstract: Metal nanostructures integrated with soft, elastomeric substrates provide an unusual platform with capabilities in plasmonic frequency tuning of mechanical strain. In this paper, we have prepared a tunable optical device, dense arrays of plasmonic nanodisks on a low-modulus, and high-elongation elastomeric substrate with a three-dimensional (3D) sinusoidal wavy, and their optical characteristics have been measured and analyzed in detail. Since surface plasmon is located and propagates along metal surfaces with sub-wavelength structures, and those dispersive properties are determined by the coupling strength between the individual structures, in this study, a 3D sinusoidal curve elastomeric substrate is used to mechanically control the inter-nanodisk spacing by applying straining and creating a frequency tunable plasmonic device. Here we study the optical resonance peak shifting generated by stretching this type of flexible device, and the role that 3D sinusoidal curve surface configuration plays in determining the tunable properties. Since only the hybrid dipolar mode has been observed in experiments, the coupled dipole approximation (CDA) method is employed to simulate the optical response of these devices, and the experimental and simulation results show that these devices have high tunability to shift optical resonance peaks at near-infrared wavelengths, which will provide strong potential for new soft optical sensors and wearable plasmonic sensors.